2002
DOI: 10.1074/jbc.m202575200
|View full text |Cite
|
Sign up to set email alerts
|

RasGRP4, a New Mast Cell-restricted Ras Guanine Nucleotide-releasing Protein with Calcium- and Diacylglycerol-binding Motifs

Abstract: A cDNA was isolated from interleukin 3-developed, mouse bone marrow-derived mast cells (MCs) that contained an insert (designated mRasGRP4) that had not been identified in any species at the gene, mRNA, or protein level. By using a homology-based cloning approach, the ϳ2.6-kb hRasGRP4 transcript was also isolated from the mononuclear progenitors residing in the peripheral blood of normal individuals. This transcript information was then used to locate the RasGRP4 gene in the mouse and human genomes, to deduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
71
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 66 publications
7
71
1
Order By: Relevance
“…Aberrant processing of mRNAs in tumor cells has been described for the MDM2, RasGRP4, SLP-65, TLE1, TLE4, MTA1 and CD44 genes and is emerging as an important characteristic of tumor cells (Bartel et al, 2002;Kumar et al, 2002;Reuther et al, 2002;Yang et al, 2002;Jumaa et al, 2003;Venables, 2004;Watermann et al, 2006) and is observed in other diseases, such as myotonic dystrophy (Charlet-B et al, 2002). In aberrant splicing, portions of exons, portions of introns or both are retained within transcripts that fail to be purged by the cellular pathways designed to scavenge abnormal mRNAs, such as nonsense-mediated decay (Culbertson, 1999;Wilkinson and Shyu, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant processing of mRNAs in tumor cells has been described for the MDM2, RasGRP4, SLP-65, TLE1, TLE4, MTA1 and CD44 genes and is emerging as an important characteristic of tumor cells (Bartel et al, 2002;Kumar et al, 2002;Reuther et al, 2002;Yang et al, 2002;Jumaa et al, 2003;Venables, 2004;Watermann et al, 2006) and is observed in other diseases, such as myotonic dystrophy (Charlet-B et al, 2002). In aberrant splicing, portions of exons, portions of introns or both are retained within transcripts that fail to be purged by the cellular pathways designed to scavenge abnormal mRNAs, such as nonsense-mediated decay (Culbertson, 1999;Wilkinson and Shyu, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…5). Each RasGRP activates either Ras or Rap1, except RasGRP3, which is unique because it facilitates exchange for both Ras and Rap1 (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…A new class of GEFs, expressed mainly in brain and T cells (5,6), is composed of at least four members: 1) RasGRP, the first member characterized as a GEF for Ras (7); 2) CalDAGI or RasGRP2, which possesses GEF activity for N-Ras, K-Ras, and Rap1 (8); 3) CalDAGIII or Ras-GRP3, which can activate both Ras and Rap 1 (9); 4) RasGRP4, recently discovered, has been shown to activate H-Ras in a cation-dependent manner (10,11). All these GRP members have a pair of atypical EF-hands (a calcium-binding motif), and the C1 domain, which represents a signature motif that is involved in the recognition of phorbol ester and diacylglycerol (DAG) (12)(13)(14).…”
mentioning
confidence: 99%